Combined effect of CuO nanofillers and DBP plasticizer on ionic conductivity enhancement in the solid polymer electrolyte PEO-LiCF3SO3 - Johan, M.R.; Fen, L.B. (Springer Verlag (Germany), 2010)
We report a new kind of polyethylene oxide, PEO-LiCF3SO3-based composite polymer electrolyte, containing active copper oxide (CuO) nanoparticles with dibutyl phthalate (DBP) prepared by solution-cast technique. The incorporation of 10 wt.% DBP and 5 wt.% CuO to the salted polymer showed a significant conductivity enhancement with maximum conductivity 2.62 x 10(-4) Scm(-1) at room temperature. This could be attributed to the increasing of amorphous phase content and structural changes in the polymer electrolyte. Arrhenius plot suggest that temperature-dependent conductivity is a thermally activated process.